The role of chain scission and chain branching in high density polyethylene during thermo-mechanical degradation - Pinheiro, L. A.; Chinelatto, M. A.; Canevarolo, S. V. (Elsevier B.V., 2004)
The mechanical and thermo-oxidative degradation of high density polyethylene (HDPE) was measured in a twin-screw extruder using various processing conditions. Two types of HDPE, Phillips and Ziegler-Natta, having different levels of terminal vinyl unsaturation were analysed. Mild screw profiles, having mainly conveying elements, have short mean residence times then profiles with kneading discs and left hand elements. Carbonyl and traps-vinylene group concentrations increased, whereas vinyl group concentration decreased with number of extrusions. Higher temperature profiles intensified these effects. The thermo-mechanical degradation mechanism begins with chain scission in the longer chains due to their higher probability of entanglements. These macroradicals then react with the vinyl terminal unsaturations of other chains producing chain branching. Shorter chains are more mobile, not suffering scission but instead are used for grafting the macroradicals, increasing the molecular weight. Increase in the levels of extrusion temperature, shear and vinyl end groups content facilitates the thermo-mechanical degradation reducing the amount of both, longer chains via chain scission and shorter chains via chain branching, narrowing the polydispersity. Phillips HDPE produces a higher level of chain branching than does the Ziegler-Natta type. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: chain scission; chain branching; high density polyethylene; twin-screw extrusion; thermo-oxidative degradation; thermo-mechanical degradation